(untitled) (Хабаршы. Психология және социология сериясы, 2026)
The article discusses various aspects of professional development of teachers in the Republic of Kazakhstan in the context of modernisation of the education sector. Particular attention is paid to factors influencing teachers’ demand for professional development, including changes in educational standards, introduction of digital technologies, updating of teaching content and requirements for teachers’ professional competencies. The aim of the study is to identify priority areas and factors that determine teachers’ needs for professional development in the context of updated educational content, with professional development (PD) being seen as a key mechanism in Kazakhstan’s school reform agenda. At the same time, there is a lack of research at the local level on specific areas in which teachers seek to strengthen their professional competencies. This study analyses the self-assessed professional development needs of teachers in general education schools and examines their variability depending on gender, age, teaching experience, qualification level and language of instruction, which is of scientific and practical importance. The research methodology used data from the international TALIS-2018 study, including responses from Kazakhstani teachers (N = 6566). Methods of contingency table analysis, comparison of mean values, factor analysis and rating analysis of identified factors were applied. The results of the study highlight the need to take into account the balanced and practice-oriented needs of teachers when organizing their professional development, as well as the importance of considering socio-demographic differences - gender, age, experience, level of education and language characteristics - when planning professional development programs. This is because effectively meeting diverse needs and developing human capital requires a differentiated approach. The results can be used in the development and improvement of professional development programs for teaching staff. Keywords: teachers, professional development, need for PD, teacher education, socio-demographic factors, TALIS.